Cash Holdings of Small and Big Firms: Corporate Governance and Financial Constraints—Evidence from an Emerging Market - Rifaqat; Shah, Waheed Ullah (Journal of Emerging Markets and Management, 2026)
Small firms often follow the financial behavior of large firms to sustain operations and mitigate risks during periods of uncertainty. This study examines the relationship between corporate cash holdings of small and large firms, while assessing the impact of corporate governance and financial constraints among 200 non-financial companies listed on the Pakistan Stock Exchange (PSX) from 2013 to 2018. Financial constraints (FC) are measured using the Altman Z-score, and corporate governance (CG) is evaluated through Board Size, Board Independence, Board Meetings, Institutional Shareholding, and Executive Shareholding. The control variables include Non-Cash Assets, Operating Cash Flow, Capital Expenditure, Net Working Capital, Sales Growth, Leverage, and Firm Size, while Cash Holdings serve as the dependent variable. Using a deductive and quantitative approach with panel data analysis (Fixed Effect Model) in EViews 9, the study finds that small and large firms exhibit a positive and significant correlation in cash-holding behavior. Financial constraints show a significant positive relationship with cash holdings, indicating that constrained firms retain more liquidity as a precautionary measure. Among corporate governance proxies, only Executive Shareholding significantly influences cash holdings, while others are insignificant. Furthermore, all control variables, except Capital Expenditure, significantly affect firms’ cash-holding levels. These findings contribute to understanding the cash management behavior of firms in emerging markets, emphasizing the combined role of governance mechanisms and financial constraints in shaping corporate liquidity decisions.